2020
DOI: 10.1097/iae.0000000000002595
|View full text |Cite
|
Sign up to set email alerts
|

More Effective Screening for Epiretinal Membranes With Multicolor Scanning Laser Ophthalmoscope Than With Color Fundus Photographs

Abstract: Purpose: To assess the ability of the multicolor scanning laser ophthalmoscope (MC-SLO) to screen for epiretinal membranes (ERMs). Methods: A retrospective cross-sectional study of 35 eyes of 32 patients with an ERM detected by optical coherence tomography and 46 eyes of 23 healthy volunteers. The detection of the ERM was graded into three visibility scores—1, not visible, 2, barely visible, and 3, clearly visible—by retina specialists or by ophthalmolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…Most of the studies using color SLO have reported higher rates of detection of retinal abnormalities compared to conventional color fundus photographs. In addition, there are also reports of clinical contributions by enabling the making of a correct diagnosis by nonspecialists [17] and improving surgical performances [22]. Recently, there has been a lot of research on artificial intelligence (AI) using fundus photographs, OCT, and OCT angiography images [36][37][38][39][40], and there is a highly likelihood that color SLO, which has high image quality with a large amount of information, will be useful for this kind of automatic diagnosis by AI.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most of the studies using color SLO have reported higher rates of detection of retinal abnormalities compared to conventional color fundus photographs. In addition, there are also reports of clinical contributions by enabling the making of a correct diagnosis by nonspecialists [17] and improving surgical performances [22]. Recently, there has been a lot of research on artificial intelligence (AI) using fundus photographs, OCT, and OCT angiography images [36][37][38][39][40], and there is a highly likelihood that color SLO, which has high image quality with a large amount of information, will be useful for this kind of automatic diagnosis by AI.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, each wavelength produces a distinctive image of the different layers of the retina [13]. The width of a scan is about 10 μm but varies with the model [17]. This is about the same as the 6 × 6 mm scan of recent Optical coherence tomography (OCT) devices, making it possible to record changes in a small area.…”
Section: Characteristics Of New Slo Devicesmentioning
confidence: 99%
See 2 more Smart Citations
“…When a wide eld color image is recorded, the original single blue, green, and red SLO images are obtained simultaneously. In the multicolor SLO, the appearance of the lesion is different for each color image because the penetration of the different colors of laser is different 18,19 .…”
Section: Introductionmentioning
confidence: 99%